Effect of Draining Volume on the Yield and Enrichment Ratio During Foam Fractionation of Greek Yogurt Whey - Y. B. Ma; J. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2018)
Foam fractionation was evaluated as a cost-effective method to add value to Greek yogurt whey (GYW), a co-product of Greek yogurt manufacturing. Two separate batches of GYW were obtained from a Greek yogurt manufacturer. Whey proteins present in GYW can be concentrated and manufactured as food ingredients using a low-cost foam fractionation. The objective of this study was to apply foam fractionation with different draining volumes to GYW and evaluate its enrichment and yield of whey protein. A benchtop foam fractionation setup was built in-house, and three different foam draining volumes were used to identify the optimal processing parameters for foam fractionation of GYW. All three levels of draining volume provided enrichment of whey protein in the foamate fraction, and the 33% draining volume resulted in the highest enrichment ratio of 1.59. The yield of the foam fractionation ranged from 41 to 52%, and several improvements can be implemented to increase the yield of the process, including the use of surfactants and enzymatic hydrolysis.
Keywords: whey protein; enrichment; novel methods; valorization